Interactive teaching of multi-user detection for DS-CDMA systems using MATLAB - Lim, , HS; Wong, , WK (2005)
This paper describes a direct-sequence code-division multiple access (DS-CDMA) multi-user detection course and presents an interactive teaching method utilizing computers to demonstrate multi-user detection in DS-CDMA systems. The basic concepts related to the topic are presented using PowerPoint slides and reinforced by means of a series of MATLAB simulations. The computational techniques in evaluating the performance of multi-user detectors are also demonstrated using MATLAB. In particular, a DS-CDMA multi-user detection tutorial and simulator have been developed using MATLAB for teaching and self-study. While teaching the course it has been observed that the understanding of the students could be greatly enhanced by using simulations anti interactive presentation skills.